The Influence of Green Consumers On Green Decisions: The Role of Green Attitude As Mediating Variable (Case Study on Fore Coffee Consumers) - Widyawati, Sri Utami; Hartoyo; Weni Novandari (Indonesian Journal of Business and Entrepreneurship, 2023)
The leading factor of Fore Coffee products is to make the product have premium prices compared to products in other coffee shops.This study aimed to determine the effect of green consumers on green decisions for Fore Coffee's environmentally friendly products through green attitudes and formulate managerial implications for increasing green decisions.Statistical analysis used is the Structural Equation Model (SEM)-PLS. PLS SEM model was used to see the effect of the relationship between the variables studied. Used sampling technique is purposive sampling with 275 respondents involved. Results of the analysis suggest that green consumer variables such as green knowledge and green concern are affecting green attitudes and green decisions. Other results point out that a green attitude mediates the relationship between green consumers and green decisions. Managerial implication of this study is Fore Coffee created marketing content that educates consumers in increasing consumer education to increase green attitude. It is expected to attract green attitudes and encourage an increasing trend of green consumers for green attitudes and green decisions. Keywords: coffeeshop, green consumers, green attitude, green decision, SEM PLS